IN TEACHING TRANSLATION, WHICH SHOULD COME FIRST: FROM ENGLISH TO INDONESIAN OR VICE VERSA? - Nurjati, Nunung (WAHANA, 2012)
Students still have difficulty translating from native language into the target language. This research is triggered by the problems faced by most sixth semester students based on their previous semester tests, in which meaning is not well transmitted. The result of the previous semester test showed that the translation from English to Indonesian was good enough but it was negative for the translation from Indonesian to English. From the problems / facts above, the question of teaching translation arises, i.e. which should be taught first teaching translation from Indonesian into English then English into Indonesian or the other way around? Conducting qualitative research, the researchers try to prove which of both methods is better applied in teaching translation.